Staphylococcal Scalded Skin Syndrome in Neonates: Case Series and Overview of Outbreaks - Charlotte M. Nusman; Charlotte Blokhuis; Dasja Pajkrt; Douwe H. Visser (MDPI AG, 2022)
Skin and soft tissue infections caused by Staphylococcus aureus (S. aureus) cover a wide spectrum of diseases in neonates, including staphylococcal scalded skin syndrome (SSSS). We describe a representative case of SSSS in neonatal twins, which despite recurrence showed a mild clinical disease course. This case was part of a small outbreak on a neonatal intensive care unit and therefore exemplifies the existence of neonatal outbreaks with skin and soft tissue infections by S. aureus. Diagnosis is generally based on the clinical picture and response to antibiotics, but can be aided by histology and cultures. Sequence-based molecular techniques are available to evaluate typing and virulence of S. aureus in outbreak or surveillance settings. The pillars of treatment are antibiotics and supportive care. Methicillin resistance remains a topic of concern, especially in outbreak settings. Our overview of numerous outbreaks of neonatal S. aureus skin infections underlines the importance of outbreak management strategies, including screening to identify the source of the outbreak, and limiting exposure through hygienic measures and establishment of physical boundaries.